Factors Associated with Promoted Proliferation of Osteosarcoma by Peptidylarginine Deiminase 4. (17th May 2021) - Guo, Jianping; Yin, Lei; Zhang, Xuezhong; Su, Peng; Zhai, Qiaoli
Abstract : Osteosarcoma is the most common type of bone malignancy, and the pathogenesis has not been entirely elucidated yet. An important deimination modification enzyme PADI4 (peptidylarginine deiminase 4) has attracted much attention in recent years for its important function in several kinds of human tumors. However, the role of PADI4 on osteosarcoma tumorigenesis remains largely unrevealed. Here, we first assessed the effect of PADI4 on osteosarcoma proliferation by the CCK8 method and colony formation assay. Ectopically expressing PADI4 positively regulates the colony formation capacity of both U2OS and Saos-2 cells. Furthermore, we explored the related mechanism and showed that PADI4 could stimulate Wnt/ β -catenin and MEK/ERK signaling in both U2OS and Saos-2 cells. Then, we detected expression of PADI4 in human tissues of osteosarcoma and revealed that differential expression of PADI4 was associated with tumorigenesis of osteosarcoma. Last, we performed the in vivo experiment in nude mice and results also showed PADI4 could affect the tumor growth. In conclusion, this work revealed that PADI4 could upregulate the proliferation of osteosarcoma, mainly via the Wnt/ β -catenin and MEK/ERK signaling pathway. This study gives us new insight into the regulation mechanism of osteosarcoma proliferation and highlights PADI4 as a promising target for osteosarcoma diagnosis and treatment.